2008
DOI: 10.1002/cne.21689
|View full text |Cite
|
Sign up to set email alerts
|

Bulbospinal neurons implicated in mesopontine‐induced anesthesia are substantially collateralized

Abstract: Microinjection of pentobarbital or other gamma-aminobutyric acid type A receptor (GABA(A)-R) active anesthetics into a brainstem region in the rat that we have called the mesopontine tegmental anesthesia area (MPTA) induces a general anesthesia-like state that includes suppression of locomotor activity, loss of the righting reflex, atonia, antinociception, and apparent loss of consciousness. The suppression of muscle tone and of nocifensive spinal reflexes suggests a direct or indirect effect at the level of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 59 publications
(102 reference statements)
1
8
0
Order By: Relevance
“…Liang et al () present images that suggest an ipsilateral predominance in the PnO following tracer injections in the lumbar spinal cord. Because a large proportion of pRS neurons in the PnO projects very medially (in the ipsilateral zone 1), it seems plausible that the contralateral predominance of the PnO projection reported by Liang et al () following cervical tracer injections and the nearly symmetrical laterality reported by Reiner et al () might have arisen from contamination of medially located axons on the side contralateral to the injection. This would label ipsilaterally projecting pRS neurons in the PnO contralateral to the tracer injection site, which would then be misinterpreted as projecting contralaterally.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…Liang et al () present images that suggest an ipsilateral predominance in the PnO following tracer injections in the lumbar spinal cord. Because a large proportion of pRS neurons in the PnO projects very medially (in the ipsilateral zone 1), it seems plausible that the contralateral predominance of the PnO projection reported by Liang et al () following cervical tracer injections and the nearly symmetrical laterality reported by Reiner et al () might have arisen from contamination of medially located axons on the side contralateral to the injection. This would label ipsilaterally projecting pRS neurons in the PnO contralateral to the tracer injection site, which would then be misinterpreted as projecting contralaterally.…”
Section: Discussionmentioning
confidence: 93%
“…Using the same dorsolateral funiculus‐targeted tracer applications, Watkins et al (1981) report bilateral labeling in PnC and contralateral labeling in PnO, again with only few pRS neurons labeled. In contrast to these studies, Reiner et al () report equal numbers of ipsilateral and contralateral pRS neurons regardless of whether injections were made at cervical, thoracic, or lumbar levels, and Liang et al () report a substantial contralateral predominance of projections from the PnO following tracer injections into the cervical spinal cord, although they do report an ipsilateral predominance for the PnC. Liang et al () present images that suggest an ipsilateral predominance in the PnO following tracer injections in the lumbar spinal cord.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Therefore, PnO must have a role in muscle relaxation during REM sleep. PnO has been shown to have spinal projections in many species [6][7][8][9][10][11] and its fiber termination in the spinal cord has also been reported in the rat [12,13] and cat [9,[14][15][16][17]. However, controversies in the projecting pattern also exist.…”
Section: Introductionmentioning
confidence: 90%